Body Image Quality of Life in Patients with Hidradenitis Suppurativa Compared with Other Dermatological Disorders - Pernille Lindsø Andersen; Rikke Maria Nielsen; Viktoria Sigsgaard; Gregor B.E. Jemec; Peter T. Riis (Medical Journals Sweden, 2020)
Hidradenitis suppurativa is a chronic skin disease characterized by inflammation and disfiguring scarring in the intertriginous body areas. Hidradenitis suppurativa is associated with overweight and impaired quality of life. This study sought to describe Body Image Quality of Life (BI-QoL) in patients with hidradenitis suppurativa and to compare it with patients with other skin diseases (controls). A total of 285 participants were recruited, 141 with hidradenitis suppurativa and 144 controls, at the Department of Dermatology at Zealand University Hospital, Denmark (during 2017-18). The Danish "Body Image Quality of Life Inventory" questionnaire measured BI-QoL. Patients with hidradenitis suppurativa had significantly lower mean BI-QoL than controls: Hidradenitis suppurativa BI-QoL (standard deviation; SD) -0.87 (0.98) vs. control BI-QoL (SD) 0.01 (1.11), p < 0.001. Predictors of negative BI-QoL were hidradenitis suppurativa, increased body mass index, female sex, symptoms of depression, and body mass index moderated by hidradenitis suppurativa. These data suggest that BI-QoL is impaired in patients with hidradenitis suppurativa compared with patients with other skin diseases after adjusting for confounders.